Tinjauan Yuridis Terhadap Pembuktian Tindak Pidana Kekerasan Psikis Dalam Lingkup Rumah Tangga - Husni Thamrin; Eli Tri Kursiswanti; Ira Pebriani (LPPM STIH Awang Long, 2021)
Domestic problems were initially seen as private issues between individuals, but the rise of domestic violence led the government to contribute to addressing the problem. One of the violence that is often accepted in the domestic is psychic violence, therefore researchers are interested in studying the analysis of the evidence of criminal acts of psychic violence in the domestic sphere. This research is an empirical juridical law study. Through a sociological juridical research approach. The research location is located in Samarinda Police, Samarinda State Prosecutor's Office, Samarinda District Court, types and sources using primary data as well as secondary data, techniques of obtaining data obtained through primary data collection techniques by interview while secondary data collection techniques are obtained from literature studies.